An investigation of a catalytically-ignited autothermal reformer pre-heating system for hydrogen production in a fuel cell powered vehicle - Razak, M. M. A.; Mustafa, A.; Nasri, N. S.; Songip, A. R. (2003)
Partial oxidation (POX), catalytic steam reforming (CSR) and autothermal reforming (ATR) are some of the main processes widely used to produce hydrogen. Autothermal Reformer also defines as a steam reforming reaction and a partial oxidation reaction that take place over microscopic distances at the same catalytic site thus avoiding complex heat exchanging. The steam reforming reaction absorbs part of the heat generated by the partial oxidation process reaction, limiting the maximum temperature in the reactor. For a catalytically ignited autothermal reformer system, catalysts need to be preheated to its light- off or catalytic ignition temperature before the reactions can be self-sustained. The objective of this research is to come out with the practical method for starting-up an autothermal reformer system in the shortest possible preheating time. A catalytic burner has been proposed to supply the required energy for pre- heating the autothermal reactor. This proposed catalytic burner will use available hydrogen and natural gas as fuel and platinum on the honeycomb monolith surface as catalyst. Platinum-type catalyst can readily reacts hydrogen with air under room temperature to produce heats that aid the catalyst to reach light off temperature. The energy from catalytic combustion will be used to preheat the autothermal reformer. Ceramic honeycomb monolith with platinum based washcoat will be used a burner system. The results will then be further verified using CFD-ACE code and as well as compared with that of conventional preheating methods such as electrical coil.